The Palaeoenvironment in Palaeolithic Bukit Bunuh: A Geomorphological Analysis - Talib, Nor Khairunnisa; Saidin, Mokhtar; Abdullah, Jeffrey (Melayu: Jurnal Antarabangsa Dunia Melayu, 2018)
Archaeological research conducted in the western part of Bukit Bunuh Complex in 2008 to 2010 uncovered two open Palaeolithic sites that function as Palaeolithic stone tools workshop. The workshop existed around 270,000-320,000 and 490,000-550,000 years ago. To determine the adaptation of Palaeolithic communities to the environment, palaeoenvironment, reconstruction studies have been conducted. The study involved interpreting the geomorphology. The results of this combined study found evidence that the ancient lakes of Chenderoh at this site was occupied during this time. This ancient lake is the same lake that existed at the time other Palaeolithic sites in the Lenggong district were occupied, such as Kota Tampan, Temelong and Bukit Jawa. However, the depth of this ancient lake was found to have fluctuated due to the influence of natural obstructions on the rivers around Lenggong. Based on this paleoenvironment reconstruction study, it was found that the Palaeolithic communities of the Middle Pleistocene at Bukit Bunuh also adapted to the lake, which was the chosen place for Palaeolithic settlements in the region. This was because the lake provided water resources, food sources and raw materials that allow for survival. Keywords: Palaeolithic, Bukit Bunuh, paleoenvironment, geomorphology, ancient lakes, adaptation